In Silico Study of Hops Plant Compounds (Humulus lupulus L.) as Phytoestrogens for Insulin Resistance - Siagian, Johanna Berliana; Hermansyah, Inas Fathinah; Pendy, Violent Irene; Wibowo, Mutia Amara Putri; Haq, Dhiya'Ul; Pramudita, Fransisca Widi; Aulifa, Diah Lia (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Postmenopausal women often experience insulin resistance, a condition linked to declining estrogen levels. Structurally similar to endogenous estrogen, phytoestrogens derived from Humulus lupulus L. (hops) hold potential as natural agents in hormone replacement strategies. This research utilized a comprehensive in silico methodology to assess 20 bioactive hop-derived compounds for their ability to act as agonists of estrogen receptor alpha (ERα). The evaluation involved Lipinski’s Rule of Five, ADME-Tox profiling, pharmacophore-based screening, and molecular docking analyses. Seven compounds satisfied the pharmacophore model criteria. Among them, Isoxanthohumol and 8-prenylnaringenin displayed the most favorable binding affinities, while Desmethylxanthohumol and Naringenin showed interaction patterns closely aligned with those of the native ligand. Although the majority demonstrated favorable pharmacokinetic properties, a few compounds presentedpotential mutagenic or carcinogenic effects. Considering binding performance, interaction resemblance, and predicted safety, these four compounds emerge as strong phytoestrogen candidates for ERα modulation in insulin resistance. Experimental validation through biological studies is necessary to substantiate these computational findings.